Effects of Plant Growth Regulators on Rooting of Tea Cuttings (Camellia sinensis) Clone 100 Iran - AZADI GONBAD, REZA; FATEMI CHOKAMI, ALI (Asian Journal of Chemistry, 2010)
A study has been carried out to evaluate root formation and growth in tea cuttings, clone 100 of Iran, soaked in solutions of some growth promoting substance such as indole-3-butyric acid (IBA) and 1-naphthalene acetic acid (NAA). An attempt has also been made to identity their optimal dosage. Rooting and plant growth parameters were improved when cuttings soaked in solutions of IBA and NAA than control. Mixture of NAA + IBA at 2000 ppm showed greatest effect than other concentrations.